Dysphagia post extubation? - Salman, Amiruddin; Fairuz, Ibrahim; Mohd Sayuti, Razali; Khairudin, Abdullah; Amran, Mohamad; Atiqah Farah, Zakaria (2018)
Intubation to protect the airway during emergency airway management rarely cause foreign body (FB) dislodgment as the operator were trained to have full visualization of the oral cavity till the laryngeal inlet before introducing the endotracheal tube. However the risk is still there as in our case that presented a young man with a complaint of dysphagia for 3 days after extubation. On laryngeal examination, we noted a dentures resembling epiglottis impacted at the post cricoid area which was successfully removed by Magill Forcep under clinic setting.